2003
DOI: 10.1086/367991
|View full text |Cite
|
Sign up to set email alerts
|

Restricted T Cell Receptor β‐Chain Variable Region Protein Use by Cornea‐Derived CD4+and CD8+Herpes Simplex Virus–Specific T Cells in Patients with Herpetic Stromal Keratitis

Abstract: Herpetic stromal keratitis (HSK) is a T helper type 1 cell-mediated inflammatory disease triggered by herpes simplex virus (HSV) infection of the cornea. In contrast to animal models of HSK, little is known about the role of T cells in human HSK. The phenotypes and repertoires of HSV-specific T cells recovered from the corneas of 12 patients with HSK were determined by flow cytometry. Cornea-derived T cell lines (TCLs) from 10 of the 12 patients contained high numbers of HSV-specific T cells. HSV reactivity wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
17
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 23 publications
1
17
0
Order By: Relevance
“…In this regard, it has been shown that 4-1BB, which has preferential effects on the survival or expansion of CD8 + T cells, is required for the development of herpes stromal keratitis (HSK) (Koelle et al, 1994;Seo et al, 2003;Verjans et al, 1998). It also has been shown that corneal bottoms isolated from HSK patients had higher numbers of HSV-reactive CD8 + T cells than HSV-reactive CD4 + T cells (Maertzdorf et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, it has been shown that 4-1BB, which has preferential effects on the survival or expansion of CD8 + T cells, is required for the development of herpes stromal keratitis (HSK) (Koelle et al, 1994;Seo et al, 2003;Verjans et al, 1998). It also has been shown that corneal bottoms isolated from HSK patients had higher numbers of HSV-reactive CD8 + T cells than HSV-reactive CD4 + T cells (Maertzdorf et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…74, 161 Although the nature of the antigens recognized by the cornea infiltrating T-cells are still unknown, parts of the cascade of inflammatory responses are elucidated by studies in 'mice and man'. 134,175,146,155,156,157,158 Development of new therapeutic strategies targeting specific HSKassociated cytokines/chemokines will be the challenge for the future to treat this sight-threatning disease more effectively. …”
Section: Summarizing Discussionmentioning
confidence: 99%
“…156 Intra-corneal TCL obtained from HSK patients contain high numbers of HSV-specific T cells. 158 Both CD4 + and CD8 + T cells are potentially involved in the intra-corneal HSV-specific T cell response. These data oppose results from studies performed in the experimental HSK mouse model in which corneal infiltrating T cells are predominantly of the CD4 + subset.…”
Section: Herpesvirus Keratitismentioning
confidence: 99%
See 1 more Smart Citation
“…The disease course in HSK begins with a primary infection by HSV followed by a period during which the virus enters latency in sensory and autonomic ganglia. Many studies have shown that clinical disease is the result of a cocktail of inflammatory cells consisting of polymorphonuclear leukocytes, macrophages and T cells (both CD4 + and CD8 + ) that are recruited to the corneas of patients with HSK (Maertzdorf et al, 2003;Pepose et al, 1996;Thomas & Rouse, 1997;Youinou et al, 1985Youinou et al, , 1986.Corneas removed from patients requiring corneal transplants due to HSK contain both CD4 + and CD8 + T cells that are specific for HSV-encoded antigens (Koelle et al, 2000). In most models of HSK, T cells are critical to the development of corneal lesions, as athymic nude mice do not display signs of HSK (Metcalf et al, 1979) unless adoptive transfer of T cells is performed (Russell et al, 1984).…”
mentioning
confidence: 99%